Dynamic Governance Bureaucracy Model for Combating Abuse of Authority: Challenges at Class IIA Curup Correctional Facility - Herisistam; Siti Aisyah; Sedarmayanti; Aziz Sanapiah (CV. Creative Tugu Pena, 2026)
This study analyzes the legal concept of abuse of authority and examines how innovative and adaptive policy practices are a form of dynamic governance approach model in the implementation of governance in the class IIA Curup correctional institution, Rejang Lebong Regency, Bengkulu. This study is a qualitative research with a literature review approach by analyzing studies related to the dynamic governance bureaucracy model and theories of abuse of authority in several journals that have been published. The results of this study explain that the abuse of authority was born because of the paradigm that considers the concept of abuse of authority cannot be completely separated from the perspective of criminal law, because authority is a core concept in the study of administrative law. This creates a gap for many parties to commit acts of abuse of authority, which in fact administrative law and related criminal laws related to the abuse of authority are complementary instruments and do not need to be opposed. Then, the dynamic governance bureaucracy model that can reduce the space for abuse of authority can be in the form of: 1) Presenting a harmonized understanding of laws and regulations on